The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5935/1678-9741.20140035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of valve prosthesis type on early mortality in patients undergoing valve surgery

Abstract: ObjectiveTo evaluate the influence of the type of prosthesis in-hospital mortality in the post-operative period in patients who had valve replacement.MethodsA cross-sectional data, such as gender, origin, age, etiology, echocardiograph data, the type of surgery performed and the prosthesis used in cases of valve replacement were analyzed retrospectively.ResultsWe reviewed 353 charts of patients who underwent valve replacement surgery. The mean age was 41.87±17.9 years. Regarding gender, 52.8% were female. As f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…[7][8][9] In addition, it is known that its prevalence is higher in the female population, 7 which has been confirmed by most studies on valve disease. 8,[11][12][13][14][15][16] As observed in the present study, mean age of patients undergoing valve replacement due to rheumatic etiology is relatively low, in accordance with previous studies. 12,15,17 On the other hand, participants of studies carried out in high-income countries are older, due to the predominance of degenerative and ischemic etiology of valve disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[7][8][9] In addition, it is known that its prevalence is higher in the female population, 7 which has been confirmed by most studies on valve disease. 8,[11][12][13][14][15][16] As observed in the present study, mean age of patients undergoing valve replacement due to rheumatic etiology is relatively low, in accordance with previous studies. 12,15,17 On the other hand, participants of studies carried out in high-income countries are older, due to the predominance of degenerative and ischemic etiology of valve disease.…”
Section: Discussionsupporting
confidence: 93%
“…Among these, while some studies 10,30 have suggested the use of bioprosthesis as a risk factor, several others have not observed worse outcomes with its use, as we have seen in the present study. 13,18,24,32 It is noteworthy that biological valves have been more frequently used than mechanical ones. The latter require anticoagulation for life, with strict control of INR, and consequently require access to health services and good treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic results demonstrated a high prevalence of several comorbidities, and procedure details showed a high occurrence of other valve interventions and surgeries associated with coronary artery bypass grafting. In addition, there is a known high prevalence of rheumatic valve disease, which is a major cause of heart disease in developing countries [ 13 ] . It was observed low late mortality (> 30 days after implant) similar to those described in the literature for other types of actual market bioprosthesis [ 14 , 15 , 16 ] .…”
Section: Discussionmentioning
confidence: 99%